(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2019)
This paper explores a transdiagnostic and ontological analysis of fatigue. Drawing on the early work of Emmanuel Levinas (2001 [1947]), this paper proposes an alternative frame for existential psychotherapists who are located within cognitive-behavioural oriented services, and working with clients who experience fatigue.